Computed tomography for diagnosis and therapeutic planning of nasopalatine duct cyst: clinical case report - Malaquias, Pietry Dy Tarso Inã Alves; Costa, Marcelo Victor Omena Caldas; Ribeiro, Igor Lerner Hora; Batista, Anaclécia dos Santos; Sarmento, Viviane Almeida; Bomfim, Rodrigo Tavares (ARCHIVES OF HEALTH INVESTIGATION, 2013)
The nasopalatine duct cyst (NPDC)is a non-odontogenic cyst that occurs in the anterior maxillary region. It’s generally painless and diagnosed through conventional radiographic examination. Enucleation is usually the surgical procedure chosen for this type lesion, but when untreated, it can reach large dimensions and require surgical procedures in hospitals. Imaging exams are fundamental to determine the extent of the injury and adjacent tissue involvement, and thus better tailor treatment for each case. Because of anatomical overlapping in some cases, conventional radiographs are not sufficient to assess tissue depth. However, by using different tools and reconstructions, computed tomography (CT) allows accurate bone and soft tissue lesion assessment, which makes it essential in many situations in dentistry. This study aims at reporting the case of a large NPDC, in which CT was vital for diagnosing and planning surgical enucleation. Keywords: Nasopalatine Duct Cyst, Cone beam CT, Jaw Cysts